Implementasi Pembelajaran Kitab Ta'limul Muta'allim Berbasis Nilai-Nilai Moderasi Beragama: Implementasi Pembelajaran Kitab Ta’limul Muta’allim Berbasis Nilai – Nilai Moderasi Beragama Disatuan Pendidikan Muadalah Ulya Blokagung Banyuwangi - Rifandi, M.Afif Rosyidi (IJIT: Indonesian Journal of Islamic Teaching, 2024)
ABSTRACT Educational institutions certainly have a certain vision and mission, in order to create or produce quality students, in the process of creating quality children. A professional teacher must have a myriad of skills in transferring knowledge to their students. Tactics, strategies and methods are the principles mastered by learners to communicate subjects to their students. So that Effectiveness is needed as a benchmark in. The objectives of this study are: (1) To describe the Implementation of Learning the Ta'limul Muta'allim Book Based on Syura' Values ​​at the Muadalah Ulya Blokagung Banyuwangi Educational Unit. (2) To describe Learning the Ta'limul Muta'allim Book Based on Tasamuh Values ​​at the Muadalah Ulya Blokagung Banyuwangi Educational Unit. (2) To describe Learning the Ta'limul Muta'allim Book Based on Qudwah Values ​​at the Muadalah Ulya Blokagung Banyuwangi Educational Unit. To answer these problems, the researcher used a qualitative approach with a case study research type. The data collection techniques used semi-structured interviews, passive participant observation, and documentation. The interactive model of Miles, Huberman, and Saldana includes data collection, data condensation, data presentation, and drawing conclusions. Data validity is carried out using credibility, transferability, dependability, and confirmability techniques. The findings of this study are: 1) Students are not only invited to understand the meaning of the book in depth, but are also encouraged to collaborate, discuss, and express their opinions. 2) The learning methods used emphasize inclusivity and tolerance. Every opinion is valued, and students are taught to accept differences of opinion with an open heart. 3) Students are required to learn to take examples from the behavior and morals of teachers as good examples, and to practice them in the daily lives of students. Keyword: Implementation, Learning the Book of Ta'limul Mutaallim, Values ​​of Religious Moderation